Factors Influencing Acceptance of E-health: an Interpretive Structural Modeling - Ruhollah Tavallaei; Mohammad Milad Ahmadi (Journal of Information Technology Management)
The aim of this study is to analyze the factors affecting the acceptance of electronic health on the basis of the theory of planned behavior. E-health is a growing field of health communication that entails using medical informatics, public health, and trades. As a result, E-health facilitates the provision of health information and services through the internet and related technologies. In this regard, this study aims to explain the acceptance of e-health by its beneficiaries such as physicians, patients, and healthcare managers. The results have shown that the most important factors affecting the acceptance of e-health are:  1. Organizational related factors of e-health services; 2. Human-related factors of acceptors; 3. Environment-related factors; 4. Factors associated with financial sources and expenditures; 5. Technical and infrastructural factors. Taking advantage of interpretive structural modeling, we demonstrated these factors and determined the level of their reciprocal relations.